2006
DOI: 10.1007/s00249-006-0091-5
|View full text |Cite
|
Sign up to set email alerts
|

Leakage and lysis of lipid membranes induced by the lipopeptide surfactin

Abstract: Surfactin is a lipopeptide produced by Bacillus subtilis which possesses antimicrobial activity. We have studied the leakage and lysis of POPC vesicles induced by surfactin using calcein fluorescence de-quenching, isothermal titration calorimetry and 31 P solid state NMR. Membrane leakage starts at a surfactin-to-lipid ratio in the membrane, R b % 0.05, and an aqueous surfactin concentration of C S w % 2 lM. The transient, graded nature of leakage and the apparent coupling with surfactin translocation to the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
192
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(200 citation statements)
references
References 43 publications
7
192
0
1
Order By: Relevance
“…In the present study, we therefore focused on the effects of surfactin on the cellular fatty acid composition of membranes to elucidate its apoptosis mechanisms. We hypothesized that lipopeptides exert their inhibitory effects by interaction with membrane or cellular fatty acids as lipopeptides can interact with membrane phospholipids and penetrate into the membrane in a concentration dependent relationship (Carrillo et al, 2003;Heerklotz and Seelig, 2007). Our experiments showed that the composition of cellular fatty acids was influenced by lipopeptides.…”
Section: Discussionmentioning
confidence: 83%
“…In the present study, we therefore focused on the effects of surfactin on the cellular fatty acid composition of membranes to elucidate its apoptosis mechanisms. We hypothesized that lipopeptides exert their inhibitory effects by interaction with membrane or cellular fatty acids as lipopeptides can interact with membrane phospholipids and penetrate into the membrane in a concentration dependent relationship (Carrillo et al, 2003;Heerklotz and Seelig, 2007). Our experiments showed that the composition of cellular fatty acids was influenced by lipopeptides.…”
Section: Discussionmentioning
confidence: 83%
“…In case of the less often observed graded mechanism [39] only a well-defined amount of dyesolution is released from the vesicles. It is not known which mechanism PLL and PLA follow.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…At high concentrations, the detergent effect prevails and it results in the disruption of the membrane. The local surfactin-to-lipid ratio (R b ) within the membrane necessary to start the leakage is R b ~ 0.05 [28]. The permeabilizing activity of surfactin is thus stronger than that of detergents such as Triton.…”
Section: Surfactin-membrane Interactionmentioning
confidence: 99%
“…Although there is only limited knowledge of the lipopeptide molecular mode of action, a few key properties have been described. A number of lipopeptides tend to aggregate into oligomers and micelles and can readily interact with the cytoplasmic membrane via their hydrophobic moieties [28,59]. Thus, these types of compounds with their unusual structures that act rapidly on membrane integrity rather than on other vital processes are a growing source of concern in modern medicine and might perhaps hold promise for the development of a new generation of antibiotics [60].…”
Section: Potential Applications Of Surfactinsmentioning
confidence: 99%